Efficacy of the Healing Effect of Topical Jayanti (Tridax procumbens) Cream versus Topical Lignocaine with Nifedipine Cream in Parikartika (Acute Fissure-in Ano): A protocol for Randomised Controlled Trial - Shubham Bobade; Sheetal Asutkar (Journal of Clinical and Diagnostic Research)
Introduction: Fissure-in-ano are a notably prevalent anorectal condition, primarily associated with ulcers and raised anal sphincter spasm. The management options largely focus on promoting wound healing and reducing anal spasm. Medical treatment, which includes a fibre-rich diet and sitz baths, results in the healing of nearly half of the fissure-in-ano. The ulcer of the anal canal is the presenting complaint in this condition. Topical Ayurvedic medicine can be utilised to heal such ulcers. Need of the Study: A review of the literature suggests that T. procumbens exhibits potent wound healing, antioxidant, antimicrobial, anti-inflammatory, procoagulant and immunomodulatory properties. Given that an acute fissure-in-ano presents as an ulcer in the anal canal, this study proposes the use of T. procumbens for its management. A im: To evaluate the efficacy of Jayanti (T. procumbens) cream versus topical Lignocaine and Nifedipine cream in the treatment Materials and Methods: A single-blind, double-arm comparative randomised control trial will be conducted at the Department of Shalyatantra, Mahatma Gandhi Ayurveda College Hospital and Research Centre (MGACHRC), Salod Hirapur (H), Maharashtra, India, from April 2023 to November 2024, with 70 subjects enrolled. In the control group, topical Lignocaine and Nifedipine cream will be applied, while in the interventional group, topical Jayanti (T. procumbens) cream will be applied to the acute fissure-in-ano. The evaluation parameters, including wound healing, anal spasm, per rectal bleeding, pain and itching, will be assessed.